2018
DOI: 10.1002/msc.1225
|View full text |Cite
|
Sign up to set email alerts
|

Women's situation‐specific strategies in managing participation restrictions due to early rheumatoid arthritis: A gender comparison

Abstract: Women and men used four types of situation-specific strategies in managing RA; adjustment, avoidance, interaction and acceptance. These situation-specific strategies provide useful knowledge, in terms of multidisciplinary rehabilitation and for patients' significant others.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
(50 reference statements)
1
4
0
Order By: Relevance
“…Participants of the current study considered remunerative and non-remunerative employment as subdomains of participation that are fundamentally different from each other, which is in line with previous research [18]. It also becomes clear from the interviews that work at home has a different meaning compared to remunerative employment, as previously suggested [19]. However, the PROMIS item bank contains items that ask respondents about the ability to partake in work, but does not distinguish between remunerative employment, non-remunerative employment, and work at home as unique forms of participation to make sure that the items are universally applicable to people, e.g.…”
Section: Discussionsupporting
confidence: 80%
“…Participants of the current study considered remunerative and non-remunerative employment as subdomains of participation that are fundamentally different from each other, which is in line with previous research [18]. It also becomes clear from the interviews that work at home has a different meaning compared to remunerative employment, as previously suggested [19]. However, the PROMIS item bank contains items that ask respondents about the ability to partake in work, but does not distinguish between remunerative employment, non-remunerative employment, and work at home as unique forms of participation to make sure that the items are universally applicable to people, e.g.…”
Section: Discussionsupporting
confidence: 80%
“…Indeed, in the present hierarchical multiple regression analysis on the mental component of HRQoL, alexithymia, the HADS‐D subscale, the Resting coping strategy, and the presence of rumination regarding pain were significant predictors of SF‐36_MC, with the final model explaining 40% of the variance. These results are in agreement with those reported by some previous studies in patients with CP, which found that patients’ coping strategies, pain catastrophizing, and mood independently contributed to the psychosocial disability adjustment, more so than the pain intensity itself (Edwards et al ., ; Lame, Peters, Vlaeyen, Kleef & Patijn, ; Östlund, Björk, Thyberg, Valtersson & Sverker, ). It is well known that depression and pain catastrophizing are two crucial psychosocial factors that influence the course and experience of chronic pain (Edwards et al ., ; Miller‐Matero, Chipungu, Martinez, Eshelman & Eisenstein, ; Morgan, ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, knowing that higher self‐efficacy scores are associated with lesser psychological distress and tiredness, underline that talking to patients about how to balance their activities and energy according to their individual situations (Grønning et al, ) is needed to support patients to become good self‐managers, (Bech et. al, , Chaleshgar‐Kordasiabi, Enjezab, Akhlaghi, & Sabzmakan, ; Dures et al, ; Ostlund, Björk, Thyberg, Valtersson, & Sverker, ) and that men and women may have different needs (Flurey et al, , , , ; Gruszczynska & Knoll, ).…”
Section: Discussionmentioning
confidence: 99%